Growth Phase-Dependent Activation of the DccRS Regulon of Campylobacter jejuni - Wösten, Marc M. S. M. (American Society for Microbiology (ASM), 2010)
Two-component systems are widespread prokaryotic signal transduction devices which allow the regulation of cellular functions in response to changing environmental conditions. The two-component system DccRS (Cj1223c-Cj1222c) of Campylobacter jejuni is important for the colonization of chickens. Here, we dissect the DccRS system in more detail and provide evidence that the sensor DccS selectively phosphorylates the cognate effector, DccR. Microarray expression profiling, real-time reverse transcription-PCR (RT-PCR), electrophoretic mobility shift assay, and primer extension analyses revealed that the DccRS regulon of strain 81116 consists of five promoter elements, all containing the consensus direct repeat sequence WTTCAC-N6-TTCACW covering the putative −35 promoter regions. One of these promoters is located in front of an operon encoding a putative macrolide efflux pump while the others are in front of genes coding for putative periplasmic or membrane proteins. The DccRS-regulated genes in C. jejuni strain 81116 are needed to enhance early in vivo growth of C. jejuni in 7-day-old chickens. The DccRS system is activated in the late stationary bacterial growth phase, probably by released metabolic products. Whole-genome mRNA profiling and real-time RT-PCR analysis under these conditions demonstrated that the system has no influence on the transcription of genes outside the DccRS regulon.